Real-Time qPCR as a Method for Detection of Antibody-Neutralized Phage Particles - Kłopot, Anna; Zakrzewska, Adriana; Lecion, Dorota; Majewska, Joanna M.; Harhala, Marek A.; Lahutta, Karolina; Kaźmierczak, Zuzanna; Łaczmański, Łukasz; Kłak, Marlena; Dąbrowska, Krystyna (Frontiers in Microbiology, 2017)
The most common method for phage quantitation is the plaque assay,which relies on phage ability to infect bacteria. However, non-infective phage particles may preserve other biological properties; specifically, they may enter interactions with the immune system of animals and humans. Here we demonstrate real-time quantitative polymerase chain reaction (qPCR) detection of bacteriophages as an alternative to the plaque assay. The closely related staphylococcal bacteriophages A3R and 676Z and the coliphage T4 were used as model phages. They were tested in vivo in mice, ex vivo in human sera, and on plastic surfaces designed for ELISA assays. T4 phage was injected intravenously into pre-immunized mice. The phage was completely neutralized by specific antibodies within 5 hours (zero pfu/ml of serum, as determined by the plaque assay), but it was still detected by qPCR in the amount of approx. 107pfu/ml of serum. This demonstrates a substantial timelapse between ‘microbiological disappearance’ and true clearance of phage particles from the circulation. In human sera ex vivo, qPCR was also able to detect neutralized phage particles that were not detected by the standard plaque assay. The investigated bacteriophages differed considerably in their ability to immobilize on plastic surfaces: this difference was greater than one order of magnitude, as shown by qPCR of phage recovered from plastic plates. The ELISA assay did not detect differences in phage binding to plates. Major limitations of qPCR are possible inhibitors of the PCR reaction or free phage DNA, which need to be considered in procedures of phage sample preparation for qPCR testing. We propose that phage pharmacokinetic and pharmacodynamic studies should not rely merely on detection of antibacterial activity of a phage. Real-time qPCR can be an alternative for phage detection, especially in immunological studies of bacteriophages. It can also be useful for studies of phage-based drug nanocarriers or biosensors.